2020
DOI: 10.3389/fpsyt.2019.01022
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Abuse in Combination With Other Drugs: Monitoring Among Methadone Patients

Abstract: Introduction: In recent years, there has been an increase in the non-medical use of psychoactive prescription drugs including pregabalin (PGB). Studies have shown that multiple drug users and patients in methadone treatment programs administered PGB at high dosages in order to achieve euphoria, reduce withdrawal symptoms, or potentiate the effects of methadone. For these reasons, accurate toxicological monitoring is required for these high-risk individuals. Materials and Methods:The present study investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
1
29
0
1
Order By: Relevance
“…In the last ten years, pregabalin has been extensively prescribed off-label for psychiatric conditions such as bipolar disorder, alcohol/narcotic withdrawal states, and ADHD, and it has entered the black market ( 25 , 26 ). The principal population at risk consists of patients with other current or past substance use disorders, mostly opioid and multi-drug users who consume pregabalin in high dosages to achieve euphoria and also to reduce withdrawal symptoms, or to potentiate the effects of methadone ( 27 ). Pregabalin use was detected for example in 10.7% ( 28 ) and 14% ( 27 ) of hair specimens from of opioid maintenance patients in Italy, and in 4 to 17.7% of urine samples from opioid maintenance patients in Switzerland ( 29 ), Ireland ( 30 ), Sweden ( 20 ), and Israel ( 31 ), while one other study found zero prevalence in hair samples ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last ten years, pregabalin has been extensively prescribed off-label for psychiatric conditions such as bipolar disorder, alcohol/narcotic withdrawal states, and ADHD, and it has entered the black market ( 25 , 26 ). The principal population at risk consists of patients with other current or past substance use disorders, mostly opioid and multi-drug users who consume pregabalin in high dosages to achieve euphoria and also to reduce withdrawal symptoms, or to potentiate the effects of methadone ( 27 ). Pregabalin use was detected for example in 10.7% ( 28 ) and 14% ( 27 ) of hair specimens from of opioid maintenance patients in Italy, and in 4 to 17.7% of urine samples from opioid maintenance patients in Switzerland ( 29 ), Ireland ( 30 ), Sweden ( 20 ), and Israel ( 31 ), while one other study found zero prevalence in hair samples ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hair was the selected modality of analysis, as it provides long-term information on drug use. It is a strong, stable tissue that is less affected by adulterants or short-term abstinence and thus has an advantage over traditional matrices (e.g., blood or urine) of being able to confirm long-term exposure to drugs over a period of weeks to months, depending on the length of the hair collected [ 20 ]. Considering that the average hair growth is 1 cm per month, a hair sample that was 3 cm in length allowed us to examine a retrospective time window of approximately 3 months [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…This has also been demonstrated with mirogabalin ( 48 ). Published literature has shown that the risk of gabapentinoid abuse increased in subjects with a history of substance use disorder, particularly in those with opioid use disorder ( 8 , 9 , 49 54 ). The present data suggest that abuse could be observed in subjects without any opioid abuse history; within the 265 spontaneous reports of gabapentinoid abuse collected, 38.7% of subjects with a substance abuse disorder had no opioid use disorder.…”
Section: Discussionmentioning
confidence: 99%